The association between influenza vaccination and hospitalization rates of respiratory and cardiovascular conditions among elderly members of a private medical scheme during the winter season of 2004 in South Africa - annevan@mweb.co.za (University of Pretoria, 2013)
Dissertation (MSc (Clinical Epidemiology))--University of Pretoria, 2007.